Klandamentalism: Bob Jones at the intersection of revivalism, politics, and white supremacy - Lewis, Camille Kaminski (Rhetoric & conflict, 2025)
"Over a decade ago, I found several rhetorical 'puzzles' sloppily hiding in my own church basement, and I've been putting them together piece-by-piece ever since. I have named this 'puzzle'--or the rhetoric at the intersection of conservative politics, revivalism, and white male supremacy--'Klandamentalism.' The founder of the infamous Bob Jones University, Bob Jones, Sr., is my representative anecdote for Klandamentalism. With nearly a terabyte of archival ephemera, I document Bob Jones, Sr.'s original rhetoric as well as the context in which he preached. The story that unfolds explains how the Ku Klux Klan made so much sense to this son of an Alabama dirt farmer. My central argument is this: Klandamentalism starts with a forceful, egocentric singular personality and a small but secret cadre of young, white males who alone act upon their neighbors, employees, families, and nation to 'bring them to God' to earn their own entry into Heaven. The words Bob Jones used in the 1920s to meld fundamentalism with the Klan parallel the white nationalistic rhetoric today. Whether the Klandamentalists are in the 1920s or 2020s, we can find better words to make a kinder, more equitable world"--Clemson University Press website